1994
DOI: 10.1136/gut.35.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Interrelations between interleukin-6, interleukin-1 beta, plasma C-reactive protein values, and in vitro C-reactive protein generation in patients with inflammatory bowel disease.

Abstract: Acute phase proteins are released from the liver in response to cytokines, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(44 citation statements)
references
References 32 publications
3
39
1
1
Order By: Relevance
“…It is strongly stimulated by interleukin-6 [1][2][3]6,7,[20][21][22][23] . Additionally, IL-1, which has been implicated in the pathogenesis of cerebral vasospasm, also provides a strong stimulus for CRP synthesis 1,[3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…It is strongly stimulated by interleukin-6 [1][2][3]6,7,[20][21][22][23] . Additionally, IL-1, which has been implicated in the pathogenesis of cerebral vasospasm, also provides a strong stimulus for CRP synthesis 1,[3][4][5] .…”
Section: Discussionmentioning
confidence: 99%
“…The present study provides evidence that the IL-6 gene is involved in determining susceptibility and disease Table 2 Functional effect of biallelic G/A polymorphism in the 4th intron of IL-6 and IL-6 VNTR polymorphism on IL-6 protein production in whole blood samples stimulated with 10 g/mL LPS for 24 h. Ulcerative colitis (UC) and Crohn's disease (CD) patients were not undergoing any steroid treatment for at least a month prior to assay (17) phenotype in Crohn's disease patients. A modest increase in the frequency of the less common IL-6*G allele was noted in Crohn's disease when compared to ulcerative colitis patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Other studies have shown that IL-6 production by isolated monocytes in vitro, both spontaneously and after LPS stimulation, is similar in IBD patients and healthy controls. 10,17 When these results were re-analysed accounting for the number of monocytes per 10 ml, the stimulated IL-6 production was increased in CD compared to UC and healthy controls. 17 We were unable to confirm any of these observations since our results showed marginally lower IL-6 production in CD patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The lower levels of coagulation intermediates or fragments in UC patients, as compared with Crohn's disease, may be simply due to more superficial distribution of intestinal inflammation always found in UC. In addition patients with Cronh's disease have higher tissue IL-1 and plasma IL-6 levels (Mazlam & Hodgson, 1994). A role of intrinsic coagulation activation pathway, associated with the contact system, in IBD is unclear.…”
Section: Systemic Coagulation Changesmentioning
confidence: 99%